2020
DOI: 10.3390/cells9030675
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Could Offer New Options to Combat the Long-Term Complications Inflicted by Gestational Diabetes Mellitus

Abstract: Gestational diabetes Mellitus (GDM) is a complex clinical condition that promotes pelvic floor myopathy, thus predisposing sufferers to urinary incontinence (UI). GDM usually regresses after birth. Nonetheless, a GDM history is associated with higher risk of subsequently developing type 2 diabetes, cardiovascular diseases (CVD) and UI. Some aspects of the pathophysiology of GDM remain unclear and the associated pathologies (outcomes) are poorly addressed, simultaneously raising public health costs and diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 217 publications
0
26
0
Order By: Relevance
“…All of them identified candidates suitable for GDM prediction. The usage of exosomes to treat GDM was suggested recently [111].…”
Section: Gestational Diabetes Mellitus (Gdm)mentioning
confidence: 99%
“…All of them identified candidates suitable for GDM prediction. The usage of exosomes to treat GDM was suggested recently [111].…”
Section: Gestational Diabetes Mellitus (Gdm)mentioning
confidence: 99%
“…Moreover, EVs derived from syncytiotrophoblast in nonpathological placenta seem to have an impact in resistance pathways of pathogen infection, and, similar to those from epithelial cells and tumors, they can be either tolerogenic or suppressive [ 226 ]. Embryo-derived EVs encapsulate nucleic acids including DNA fragments, microRNA, long non-coding RNA, messenger RNA, and a variety of proteins that can be taken over by cells of the maternal vascular and immune systems and subsequently modulate the pregnancy changes related to maternal physiology [ 227 ]. Various studies have demonstrated that the transmission of some viruses to the fibroblast and endothelial compartments is mediated by the miRNA cluster of the chromosome 19, a cluster which is only expressed in the human placenta, overall limiting the infection by induced autophagy in recipient cells [ 228 ].…”
Section: Viral Infections During Pregnancymentioning
confidence: 99%
“…Placental tissue-derived EVs may exert effects on insulin sensitivity in normal and gestational diabetes mellitus pregnancies. Taken together, EVs offer new options for the treatment of gestational diabetes mellitus [ 81 ]. EV-encapsulated noncoding RNAs can also serve as biomarkers for the diagnosis and treatment of gestational diabetes mellitus [ 82 ].…”
Section: Evs and Pregnant Disordersmentioning
confidence: 99%